Studi Etnofarmakologi Obat Tradisional Tekanan Darah Tinggi Di Desa Onepute Kecamatan Petasia Barat Kabupaten Morowali Utara - Sakaria, Hamra; Rumi, Amelia; Masyita, Andi Atirah (Journal of Islamic Pharmacy, 2021)
High blood pressure is one of the main risk factors for cardiovascular disease which causes 20- 50% of all deaths. The people of Onepute, West Petasia District, North Morowali Regency have a very high percentage of high blood pressure with a percentage of 65%. One of the risk factors for high blood pressure is consuming foods high in fat and salt, medicinal plants are plants or parts of plants commonly used by Indonesian people as an alternative to treat various diseases. The purpose of this study was to determine the types and parts of plants used, processing, how to use, the rules of use or the dosage of treatment, as well as the compatibility between empirical knowledge of the Onepute community, West Petasia District, North Morowali Regency with ethnopharmochological studies that had been previously researched. The research method used was purposive sampling method, namely the technique of taking members of the sample from the population with certain considerations. The research was conducted by means of semi-structured interviews with open questions to 6 sandro people of the Onepute community, West Petasia District, North Morowali Regency and the form of data presentation in a qualitative way. The results showed that there were 6 types of plants, and what is widely used by the community is leaves with a percentage of 66.67%. Plant parts used include leaves, fruit and rhizomes. The processing method is boiled, squeezed, brewed and direct consumption. Compounds that play a role in lowering high blood pressure are monotetrahydrofuran acetogenin compounds, such as anomuricin A and B, gigantetrosin A, annonasin-10-one, muricatosin A and B, annonacin, and goniothalamicin, postasium, potassium, gingerol, shogaol, sodium, flavonoids, tannins, triterpenoids, saponins, polyphenols.Keywords: Ethnopharmacology, High Blood Pressure Disease, Onepute Society.